2019
DOI: 10.1093/ehjci/jez207
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive in vivo imaging of acute thrombosis: development of a novel factor XIIIa radiotracer

Abstract: Aims Cardiovascular thrombosis is responsible a quarter of deaths annually worldwide. Current imaging methods for cardiovascular thrombosis focus on anatomical identification of thrombus but cannot determine thrombus age or activity. Molecular imaging techniques hold promise for identification and quantification of thrombosis in vivo. Our objective was to assess a novel optical and positron-emitting probe targeting Factor XIIIa (ENC2015) as biomarker of active thrombus formation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…Ultrasound imaging can now use microbubbles and other contrast agents coated with specific targeting ligand molecules that bind selectively to the site of interest 14 . Thrombus‐targeted imaging technologies use ligands that are specific either for fibrin, 15 activated platelets expressing the integrin αIIbβ3, 16 or prothrombotic components such as factor XIIIa, 17 tissue factor, von Willebrand factor, or exposed collagen 14 . Noninvasive molecular imaging techniques targeting thrombus components have been used both in disease‐state animal models and in clinical applications.…”
Section: Visualizing Thrombi In Vivo and Ex Vivomentioning
confidence: 99%
“…Ultrasound imaging can now use microbubbles and other contrast agents coated with specific targeting ligand molecules that bind selectively to the site of interest 14 . Thrombus‐targeted imaging technologies use ligands that are specific either for fibrin, 15 activated platelets expressing the integrin αIIbβ3, 16 or prothrombotic components such as factor XIIIa, 17 tissue factor, von Willebrand factor, or exposed collagen 14 . Noninvasive molecular imaging techniques targeting thrombus components have been used both in disease‐state animal models and in clinical applications.…”
Section: Visualizing Thrombi In Vivo and Ex Vivomentioning
confidence: 99%
“…Analytical HPLC was performed on a Dionex UltiMate 300 using an Agilent Pursuit XRs 5 μm C 18 column (250 × 4 mm). All precursors were purchased from Advanced Biochemical Compounds (ABX), apart from ENC2015 and ENC2018, which were manufactured as described previously 26 . The structures of all radiotracers prepared in this study are shown in Supplementary Figure 1 The radiosynthesis of the Al 18 F-labelled peptides was carried out using an automated synthesis on a GE TRACERlab MX synthesiser.…”
Section: Methodsmentioning
confidence: 99%
“…[ 18 F]AlF-NOTA-RGDfK was obtained in 11 ± 2% radiochemical yield (starting from 21 ± 2 GBq of [ 18 F]fluoride, n = 18) with a radiochemical purity of > 99%. [ 18 F]ENC2015 radiochemical yield and purity were as previously reported 26 . [ 18 F]ENC2018 was obtained in 10 ± 4% radiochemical yield (starting from 17 ± 0.4 GBq of [ 18 F]fluoride, n = 3) with a radiochemical purity of > 99%.…”
Section: Methodsmentioning
confidence: 99%
“…These typically combine a targeting component, that ideally interacts specifically with the biochemical process being investigated, and an imaging component that can attach to the targeting component without affecting its interaction with the targeted biochemical process (5). In studies of atherosclerosis, unique molecular imaging agents have been developed for the assessment of a wide variety of FIGURE 1 | Molecular and Non-molecular thrombosis imaging strategies in atherosclerosis patients for assessing pathophysiological features related to early thrombosis at the molecular and cellular level (13), including ultrasound molecular imaging (6), magnetic resonance imaging (7), radionuclide imaging (14), optical imaging (15), intravascular ultrasound, optical coherence tomography, CT angiography (16), angioscopy and angiography (17).…”
Section: Non-molecular and Molecular Imaging Modalitiesmentioning
confidence: 99%